Short Communication: Genetic structure of Longtail Tuna Thunnus tonggol (Bleeker, 1851) in Java Sea, Indonesia - M. DANIE AL MALIK; NI PUTU DIAN PERTIWI; ANDRIANUS SEMBIRING; NI LUH ASTRIA YUSMALINDA; ENEX YUNIARTI NINGSIH; IDA AYU ASTARINI (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Al Malik MD, Pertiwi NPD, Sembiring A, Yusmalinda NLA, Ningsing EY, Astarini IA. 2020. Short Communication: Genetic structure of Longtail Tuna Thunnus tonggol (Bleeker, 1851) in Java Sea, Indonesia. Biodiversitas 21: 3637-3643. Thunnus tonggol (Longtail Tuna) is an economically important fish found in Indonesia waters, however, the information regarding this fish is lacking. Known to be a neritic fish and found in shallow water, Java Sea is one of the ideal habitats for T. tonggol species. Due to high fishing rates activities in Java Sea, a better management plan to ensure the conservation and fisheries sustainability around this area is needed, especially to protect T. tonggol population. In order to complete the Indonesian tuna data, we aim to study the diversity and genetic structure of T. tonggol in Java Sea at three different locations; i.e. Semarang, Banjarmasin, and Jakarta. In this study, population genetic methods with the marker of mitochondrial DNA (mtDNA) control region were used in population structure analysis. A total of 115 specimens were collected from the fish market around the area of study locations and amplified using polymerase chain reaction (PCR) and sequenced using Sanger methods. The result showed genetic diversity (Hd) value of 0.99366, and nucleotide diversity (?) value of 0.01906. Both of these values indicated high genetic diversity. Population analyses using Analysis of Molecular Variance (AMOVA) showed nonsignificant differences between the three populations of study (mixing population), with the ?ST value of 0,00375 (p-value > 0.05). Based on this result, the fisheries management for T. tonggol in Java Sea needs to be managed as one single population management.